Tratamento de superfície com silicato de sódio para concreto: penetração de cloretos e absorção de água - Medeiros, Marcelo H. F.; Pereira, E.; Helene, P. (Revista ALCONPAT, 2012)
Na2SiO3 is one of several types of surface treatment for concrete. It reacts with the NaOH present in the pore solution of the concrete resulting in insoluble compounds. The aim of this paper is to describe the effect of Na2SiO3 on the transport of water and chloride ions through the concrete. To this end, results of capillary water absorption, immersion water absorption and chloride migration are presented. Results indicate that this treatment decreases the water penetration through the concrete, with a role in the corrosion kinetics of reinforced concrete. However, the results of water absorption by immersion indicated that this product should not be applied in cases where there is water pressure, that is, when the permeability is the mechanism of water penetration. Finally, it was shown that treatment with Na2SiO3 reduces the diffusion coefficient chloride resulting in increased service life of concrete structures.Keywords: concrete; surface protection; sodium silicate; durability; service life.